Students as a Teaching Resource in Preparing Educational Leaders: An International Masters Programme - Qiang Liu; David A. Turner (Educational Considerations, 2016)
The Institute of International and Comparative Education, Beijing Normal University has offered a Masters Program in Educational Leadership and Policy (Comparative Education) for the last four years and it attracts students from around the world, with substantial support in terms of scholarships, from the Chinese government. Beijing Normal University introduced a PhD programme in the same discipline in 2013. The programme is intended to train talented individuals from all over the world, and to provide them with theoretical understanding and skills that will prepare them to take positions of leadership. The programme benefits from the high calibre of students that it attracts, and a multi-national multi-cultural student body is an important educational resource. The authors have worked in the programme, with other colleagues, since its inception, and describe some of the unique features of the programme, as well as some of the challenges.
Keywords: international students; financial assistance; educational reform; Beijing Normal University; programme; education; International Leadership; curriculum; different models; management; Organisational Structure; teaching; resources